Activity › Discussion › Math › Maths › Reply To: Maths

::
To solve for x in the equation:2(x + 5) – 3 = 4(x + 2) – 7We will follow these steps:
 Distribute the coefficients on both sides
 Combine like terms on each side
 Subtract the terms with x from both sides to isolate x
 Divide both sides by the coefficient of x to find the value of x
Step 1: Distribute the coefficients on both sides
2(x + 5) – 3 = 4(x + 2) – 72x + 10 – 3 = 4x + 8 – 7
Step 2: Combine like terms on each side
2x + 7 = 4x + 1
Step 3: Subtract the terms with x from both sides to isolate x
2x + 7 = 4x + 12x 2x x = 1
Step 4: Divide both sides by the coefficient of x to find the value of xx = 1
x = 1
Therefore, the value of x that satisfies the equation 2(x + 5) – 3 = 4(x + 2) – 7 is x = 1.
<div>
</div>